Memaknai Fashion dalam Hukum Islam - Ilyas, Musyfikah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
The need clothes that bring benefit serves as a cover nakedness, over the times fashion became an icon for Muslim identity as identity, nation and civilization. Islam has instilled the values of philosophy as well as being bargading position for Muslims.